Mineral Analysis in Dioscorea hispida Dennst. Tuber by Atomic Absorption Spectrophotometry - Rehulina Gultom; Masfria; Prayoga, Tedy (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
ABSTRACT Objective: The purpose of this study was to analyze minerals in gadung (Dioscorea hispida Dennst.) tuber. Method: The analysis of minerals was conducted by using atomic absorption spectrophotometry. Results: The results showed that the concentration of iron, cadmium, potassium, calcium, sodium, magnesium, copper and zinc were 0.6445 + 0.0029 mg/100g, 0.0011 + 0.0083 mg/100g, 265.2780 + 0.4652 mg/100g, 5.1015 + 0.0490 mg/100g, 8.3011 + 0.0974 mg/100g, 29.0237 + 0.0706 mg/100g, 0.1110 + 0.0019 mg/100g, and 0.6113 + 0.0026 mg/100g, respectively. Conclulsion: The gadung (Dioscorea hispida Dennst.) tuber contains iron, cadmium, potassium, calcium, sodium, magnesium, copper and zinc as the minerals.